PENGARUH INSENTIF DAN JAMINAN SOSIAL TERHADAP KINERJA KARYAWAN UNIT SHARED SERVICE PT. TELKOM AKSES AREA RIAU DARATAN - Yoranda, Putriany; Karneli, Okta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the effect of incentives and social security on the performance of shared service PT. Telkom Access Riau Area. The independent variable consists of incentives (X1) and social security (X2). While what is used as the dependent variable (Y) is performance. The study used a questionnaire with a measurement scale using a Likert scale. The analysis technique used is simple linear regression, multiple linear regression, coefficient of determination test, t test, and f test. Data analysis using linear regression analysis with the help of SPSS 16 software.The population in this study were 37 employees of the shared service unit of PT. Telkom Access Riau Riau Area where the whole is sampled using the census method. From the results of tests conducted indicate that incentives have a positive and significant effect on performance, social security has a positive and significant effect on performance, and incentives and social security have simultaneous effects on performance. Keywords: Incentives, Social Security, Performance.